Students’ Readiness to Enter Tourism Industry - Rina Kurniawati (Institut Pariwisata dan Bisnis Internasional, 2015)
Sahid Institute of Tourism is one of the higher educations that facilitate scholarship program for students from Eastern part of Indonesia. It has more than 150 students from NTT, Papua, Gorontalo, and Ternate. At the end of their bachelor study, the students are expected to operate well in tourism industry. This research is a pilot study to investigate students’ perception on their readiness to enter tourism industry and to find out whether there is significant difference in the perception. A sample of 15 students are taken out of 76 Nusa Tenggara Timur students who are about to graduate. The sample is taken using random sampling method. A questionnaire is carried out to obtain primary data. The questionnaire consists of two parts; profile of the respondent and perception on their readiness to enter tourism industry. Six components of employability skills included. Overall students perceive that they are ready to enter tourism industry. The respondents perceive that they are ready in problem solving, independent learning, use of technology, and teamwork. They feel almost ready in use of foreign language and planning-organizing. It is found out there is no significant difference in their perception in terms of study program and gender. It is suggested that further investigation is needed.